PENGARUH KUALITAS SUMBER DAYA MANUSIA, PERENCANAAN DAN KUALITAS DIPA TERHADAP PENYERAPAN ANGGARAN DI WILAYAH KERJA SATUAN KPPN PONTIANAK - Rika, Marsiana (MAKSI UNTAN, 2018)
The aim of this research was to analyze the influence of the quality of human resources, planning and the quality of DIPA (Budget Implementation Document) toward budget absorption of working unit in the KPPN Pontianak working area either simultaneously or partially. The data used in this research was primary and secondary data. The probability sampling technique was used with 150 employees of KPPN working unit in Pontianak as the respondents. This research use the quantitative data obtained from questionnaires and applies statistical product and service solution (SPSS) version 19 as the analytical tools. The result of this research simultaneously showed that the quality of human resources, planning and the quality of DIPA had significant on budget absorption in KPPN Pontianak. The result of partial test showed that the quality of human resources and planning has positive and significance effect towards budget absorption in the unit of KPPN Pontianak. Meanwhile, the quality of DIPA had negative significant effect on budget absorption in the unit of KPPN Pontianak.Key Words: Quality of human resources, Planning, Quality of Budget Implementation Registration Form (DIPA) and Budget Absorption